COINS IN ARCHAEOLOGICAL CONTEXT (V). THE VILLA RUSTICA FROM RAPOLTU MARE – ”LA VIE” (HUNEDOARA COUNTY, ROMANIA) - Cristian GĂZDAC; Marius BARBU; Andrei GONCIAR (Journal of Ancient History and Archaeology)
The present paper is focusing on another case in the series Coins in archaeological context. The case under study is the farmstead/villa rustica from Rapoltu Mare – La vie (Hunedoara County, Romania) in the former Roman province of Dacia. Based on the correlation between archaeological, artefact data and the numismatic evidence, the paper indicates that single coin finds are distributed by layers according to the site stratigraphy.